Staged Concrete Bridge Deck Pours Adjacent to Live Traffic - Weatherer, Peter J. (My University, 2018)
Highway bridges are some of the most common and frequently used structures in today’s built environment, but they are also some of the most heavily demanded. Decades of heavy traffic loading and harsh environmental conditions cause concrete bridge decks to degrade over time, requiring them to be repaired or replaced. Additionally, ever increasing traffic demands mean that aging infrastructure needs to be updated and expanded, all while minimizing the disruption to road users. For this reason, staged construction, where traffic is maintained on the bridge while it is constructed in phases, is often turned to for bridge replacements, rehabilitations, and widenings. However, certain concerns exist with the use of staged construction. When cast-in-place concrete decks are used with staged construction, the concrete deck must cure while subjected to loads and displacements caused by the adjacent traffic using the same structure. There is concern that as the concrete hardens and turns from a fluid to a solid, traffic-induced displacements and vibrations will damage the freshly placed concrete and/or its bond with the embedded reinforcement. This research focused on evaluating the integrity and performance of longitudinal construction joints in highway bridge decks that are subjected to traffic-induced differential deflections during curing. This research included a survey of regional transportation officials, in which common practices, procedures and concerns were examined. The survey showed that staged construction is often preferred by various stakeholders, but no consistent measures are taken to limit damage to curing bridge decks and longitudinal construction joints often do not perform adequately. Visual inspections of several Wisconsin highway bridges were also performed, with a majority showing only minor signs of distress which may or may not be attributed to the staged construction process. Some minor defects were seen, such as underconsolidated concrete in the construction joint region and leakage through the joint itself. Eight structurally “identical” haunched slab bridges showed severe deterioration at the construction joints, but it was impossible to determine the exact cause of the damage through visual inspection. Differential displacements due to live traffic were measured in two prestressed concrete girder bridges during staged construction. The resulting maximum differential deflections were almost always less than 0.030 in., and on average between 0.015 in. and 0.020 in. These two bridges were similar structurally with comparable main span lengths, so it was reasonable that the magnitudes of differential deflections were also similar. Finite element analyses were performed for the same two bridges that were instrumented during construction to see if differential deflections could be accurately estimated. A truck loading was selected that would produce an upper-bound estimate of differential deflections, which was approximately 0.065 in. for both bridges. For comparison, a third model was created for a longerspan steel plate girder bridge that carried more traffic lanes during construction. In this case, larger differential deflections were predicted, up to 0.35 in., but it was shown that reducing the number of loaded traffic lanes would reduce this considerably. Finally, two concrete bridge deck test specimens were constructed using a simulated staged bridge construction process. The two specimens were subjected to different magnitudes of differential deflections during curing, after which they were subjected to an ultimate flexural strength test. Strain data from the reinforcing bars spliced at the construction joint showed that the concrete-bar bond was adequate to develop the yield strength of the reinforcement, even when the specimen was subjected to exceptionally large differential displacements during curing. Testing also showed that under bending there was a tendency for rotations to be localized at the ends of the lap splice, which could potentially cause long-term durability issues.
Keywords: differential deflections; concrete bridge decks; longitudinal construction joint; staged bridge construction